2013
DOI: 10.4039/tce.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Stenodiplosis (Diptera: Cecidomyiidae) on florets of the invasive common reed (Phragmites australis) and its effects on seed production

Abstract: A new species of gall midge, Stenodiplosis phragmicola Sinclair and Ahee (Diptera: Cecidomyiidae), is described. The host plant, Phragmites australis (Cavanilles) Trinius ex Steudel (Poaceae), is a tall, widely distributed emergent aquatic macrophyte. An introduced subspecies of the plant is considered invasive in North America (although a native subspecies also occurs). Insect specimens were collected during September 2010 and 2011 from the florets of common reed at 12 sites around Peterborough, Ontario, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…This can be considered a high prevalence compared to other similar species. For example, Ahee et al (2013) found a mean prevalence of 9.5% of Stenodiplosis phragmicola Sinclair and Ahee, a gall midge of the supertribe Cecidomyiidi that feeds on seeds of Phragmites australis. In our population, viability of the remaining intact seeds was not affected.…”
Section: Spanolepis Selloanae Effects On the Host Plantmentioning
confidence: 99%
“…This can be considered a high prevalence compared to other similar species. For example, Ahee et al (2013) found a mean prevalence of 9.5% of Stenodiplosis phragmicola Sinclair and Ahee, a gall midge of the supertribe Cecidomyiidi that feeds on seeds of Phragmites australis. In our population, viability of the remaining intact seeds was not affected.…”
Section: Spanolepis Selloanae Effects On the Host Plantmentioning
confidence: 99%